Paclitaxel-Loaded Polylactide/Polyethylene Glycol Fibers with Long-Term Antitumor Activity as a Potential Drug Carrier for Local Chemotherapy - Plch, Johana; Venclikova, Kristyna; Janouskova, Olga; Hrabeta, Jan; Eckschlager, Tomas; Kopeckova, Katerina; Hampejsova, Zuzana; Bosakova, Zuzana; Sirc, Jakub; Hobzová, Radka (Macromolecular bioscience, 2018)
Local application of anticancer agents prolongs the presence time and increases the concentration of drug in the target place and therefore may reduce serious side effects compared to drug systemic administration. The preparation of fibrous materials of polylactide (PLA) and polyethylene glycol (PEG) loaded with paclitaxel (PTX, 1 or 10 wt%) is presented. Scanning electron microscopy proves that PTX is homogeneously incorporated into the fibers. The addition of PEG of various molecular weights (6, 20, or 35 kDa) ensures the release of significantly higher amounts of hydrophobic PTX in a prolonged release time compared to the fibers containing PTX only. Present PLA-PEG fibrous carriers can serve as a drug depot for PTX since they exhibit significant toxicity for cancer cell lines in several-day experiment. They are promising for local recurrence therapy, where the initial release is efficient to kill tumor cells and continued release can prevent their subsequent proliferation.
Keywords: Neoplasms; MFC-7 buňky; Paclitaxel; nádory; nosiče léků; Drug Carriers; Polyesters; polyethylenglykoly; Polyethylene Glycols; lidé; léky s prodlouženým účinkem; Delayed-Action Preparations; Antineoplastic Agents; MCF-7 Cells; protinádorové látky; polyestery; paclitaxel; Humans